Quality of Institutions for Global Knowledge-based Economy and Convergence Process in the European Union - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2015)
The use of the potential of economic convergence is one of the key challenges of economic policy in case of European Union. Due to structural changes that have led to the growing role of knowledge-based economy (KBE), the analysis made in the paper is based on the assumption that the convergences process of the EU countries takes place in the reality of the KBE, thus in order to facilitate it, all the EU members should concentrate on building institutions that are adequate to the conditions of the KBE. In this context, the aim of the study is to verify the potential impact of the quality of institutional system of the EU countries on the process of convergence. In this regard, the analytical framework of conditional ß-convergence was used with econometric dynamic panel modeling. To measure the quality of institutional system the authors proposed original synthetic indicator, which was designed with TOPSIS method. For this purpose the data was obtained from the Fraser Institute database. Dynamic panel econometric analysis carried out for the European Union countries in the years 2004-2010 confirms that the high quality and adequacy of the institutional system to the conditions of the KBE supports convergence process in the EU.
Keywords: D02; O47; 330; institutional economics; quality of institutional system; global knowledge-based economy; conditional ß-convergence; dynamic panel analysis